Motivation of patients with inflammatory bowel disease to participate in a clinical trial - Gehrmann, U.; Berger, U.; Teich, N.; Bruns, T.; Stallmach, A.; Weber, M. (Zeitschrift für Gastroenterologie, 2016)
Background: Clinical trials are designed to investigate innovative diagnostic and therapeutic strategies for patients. However, factors that influence patients with inflammatory bowel disease (IBD) and willingness to participate in a clinical trial are unknown.Methods: We developed a questionnaire and asked IBD patients about their willingness to hypothetically participate in a clinical trial and their current health-related quality of life by using the IBDQ.Results: Of 201 distributed questionnaires, 166 were returned and included in the analysis. One-hundred-one (61 %) patients declared their willingness to participate in a clinical trial hypothetically offered in their current situation, whereas 65 (39 %) declined. Among all patients, a trustful relationship between patient and doctor was most important for trial participation. The willingness to help others and to support medical progress were other key issues mentioned. In contrast, those patients inclined to refuse trial participation feared impairment of their current health status, potential side effects, medical examinations, and the expenditure of time and effort.Conclusion: In our cohort of IBD patients, approximately two-thirds were willing to participate in a clinical trial. We were able to identify a number of factors that should help physicians to directly address fears and break down barriers in order to increase the number of patients willing to participate in clinical trials.
Keywords: Chronisch-entzündliche Darmerkrankungen; Motivation; Klinische Studien; Gesundheitsbezogene Lebensqualität